Non-technical factors on ophthalmology education: a narrative review - Jiang, Yang; Jiang, Hanyu; Yang, Zhikun; Li, Ying; Chen, Youxin (Frontiers in Medicine, 2024)
Ophthalmology education is increasingly influenced by non-technical factors. This paper examines the multifaceted influences on ophthalmology education, focusing on direct and indirect factors that have shaped the training and well-being of ophthalmology students and residents. A systematic search of PubMed and Embase was carried out, searching date was from inception to 01/07/2024. A total of 8232 articles were screened, of which 7976 were excluded following abstract review. After reading the remaining 256 articles in full, a further 228 were excluded. A total of 28 original articles were included in this systematic review. The non-technical factors that influenced ophthalmology education included various crisis, inadequate 2 curricular time, training resources, lack of training standardization and shortage of financial support and teaching resources. The review summarizes the influences on ophthalmology education of various non-technical factors, thereby helping educators improve the training methods.